Selenium levels in clinically healthy Iraqi stray cats in Baghdad city: Wasan A. Gharbi AL-Dulimy and Ahmed N. Awad AL-Ani - AL-Dulimy, Wasan A. Gharbi (The Iraqi Journal of Veterinary Medicine, 2016)
The aim of this study was to measure the selenium level in the stray cats of both sexes. Blood samples were collected from forty four male and female stray cats from different places in Baghdad city for the estimation of selenium level. The results showed that the lowest value was 1.646 μmol/L (0.13 μg/ml (ppm)) and the highest value was 3.798 μmol/L (0.3 μg/ml (ppm)) with a mean value ± Standard Error of 2.526 μmol/L ± 0.091 (0.1995 μg/ml (ppm)± 0.007). The range in males and females was 1.646 - 3.798 μmol/L (0.13 - 0.3 μg/ml (ppm)) and 2.405 - 3.798 μmol/L (0.19 - 0.3 μg/ml (ppm)), respectively with a mean 2.45 μmol/L ± 0.108 (0.194 μg/ml (ppm)± 0.009) and 2.785 μmol/L ± 0.137 (0.22 μg/ml (ppm)± 0.011) for males and females respectively .There were no significant differences between sexes under level (P≤ 0.05). The selenium concentration in blood of local Iraqi cats was within the international lowest limit of these ranges.